2016
DOI: 10.3109/10903127.2015.1128027
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Errors Using Two Length-Based Tape Systems for Prehospital Care in Children

Abstract: Background: The use of a length/weight-based tape (LBT) for equipment size and drug dosing for pediatric patients is recommended in a joint statement by multiple national organizations. A new system, known as Handtevy™, allows for rapid determination of critical drug doses without performing calculations. Objective: To compare two LBT systems for dosing errors and time to medication administration in simulated prehospital scenarios. Methods: This was a prospective randomized trial comparing the Broselow Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 40 publications
(51 reference statements)
0
13
0
1
Order By: Relevance
“…28 However, a recent simulation study found a high rate of error by paramedics administering epinephrine according to 2 different length/weight-based tapes (Broselow, 21.3% vs Handtevy, 16.3%). 29 Pediatric epinephrine dosing in the prehospital setting is known to be error prone, even with standardization. 30,31 Computerized provider order entry (CPOE) with or without clinical decision support has been widely advocated for reducing prescribing errors.…”
Section: Discussionmentioning
confidence: 99%
“…28 However, a recent simulation study found a high rate of error by paramedics administering epinephrine according to 2 different length/weight-based tapes (Broselow, 21.3% vs Handtevy, 16.3%). 29 Pediatric epinephrine dosing in the prehospital setting is known to be error prone, even with standardization. 30,31 Computerized provider order entry (CPOE) with or without clinical decision support has been widely advocated for reducing prescribing errors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have recommended a length-based tape to adjust equipment size for pediatric patients in prehospital settings. 9,12 The equipment required for prehospital care may vary according to the needs of the population being treated and training level of the ambulance crew who provides the care. Upper airway obstruction and hypoxia are major causes of death, and 0.7% of all pediatric injury patients transferred by ambulance have injury-related out-of-hospital cardiac arrest; thus, pediatric devices to maintain airway and ventilation are essential.…”
Section: Discussionmentioning
confidence: 99%
“…However, our study revealed that only 5% of the fire defense headquarters had the complete set of cuffs with appropriate sizes for children of all ages. Previous studies have recommended a length‐based tape to adjust equipment size for pediatric patients in prehospital settings 9,12 …”
Section: Discussionmentioning
confidence: 99%
“…14 Nevertheless, such errors still occurred and difficulties in using this system have been described. 15 Since the BT was never sold 16 nor licensed as a medical product in Europe it was additionally unsuitable for its use in Europe. We therefore developed and introduced a certified and licensed length-based dosing recommendation system the "Pediatric emergency ruler" (PaedER; Alpha 1 e.K., Falkenberg, Germany) in 2008.…”
Section: Introductionmentioning
confidence: 99%